Potatoes Uganda: Climate risk assessment - Duku, Confidence; Groot, Annemarie; Demissie, Teferi Dejene; Oroma, George W.; Osumba, Joab J.L. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Uganda’s agricultural sector is an important catalyst for economic growth, poverty alleviation, and food security. Nevertheless, the economic losses from the impacts of climate change on the agricultural sector by 2050 are estimated to be about US$1.5 billion (Zinyengere et al., 2016). Climate-smart agriculture practices present an opportunity to reduce such losses through building resilience in the agriculture sector, improving productivity and farmer incomes, and contributing to climate change mitigation (CIAT & World Bank, 2017). Potato is an important crop for food and income generation in Uganda, and was recognized in the 2010/11- 2014/15 Development Strategy and Investment Plan (DSIP) as a strategic commodity with the potential to make a remarkable contribution both to increasing rural incomes and livelihoods and to improving food and nutrition security. Despite its potential, sustainable intensification levels remain very low in the potato sub-sector, translating into low average yield. Farmers increase production by expanding the land used to grow potatoes, not by sustainably intensifying their activities. According to FAO statistics, the annual potato output in Uganda is approximately 800,000 metric tons, produced on approximately 112,000 hectares (FAOSTAT, 2014).